2017
DOI: 10.1016/s2213-8587(17)30313-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety and efficacy of the PCSK9 inhibitor evolocumab in patients with and without diabetes and the effect of evolocumab on glycaemia and risk of new-onset diabetes: a prespecified analysis of the FOURIER randomised controlled trial

Abstract: Amgen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
372
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 511 publications
(414 citation statements)
references
References 25 publications
28
372
1
13
Order By: Relevance
“…Consistent with the overall patient populations mentioned above,63, 78 subanalyses by diabetes mellitus status demonstrated that overall alirocumab/evolocumab safety was comparable to that of control in those with and without diabetes mellitus 66, 67, 69, 71, 80. Overall safety was also comparable versus control between patients with diabetes mellitus and ASCVD,68 insulin‐treated patients with diabetes mellitus in the DM‐INSULIN study,75 patients with T2D and mixed dyslipidemia in the DM‐DYSLIPIDEMIA study,77 individuals with prediabetes and normoglycemia,72 and those with and without dysglycemia or metabolic syndrome 73.…”
Section: Safety Of Pcsk9 Inhibitors In Patients With Diabetes Mellitusupporting
confidence: 70%
See 4 more Smart Citations
“…Consistent with the overall patient populations mentioned above,63, 78 subanalyses by diabetes mellitus status demonstrated that overall alirocumab/evolocumab safety was comparable to that of control in those with and without diabetes mellitus 66, 67, 69, 71, 80. Overall safety was also comparable versus control between patients with diabetes mellitus and ASCVD,68 insulin‐treated patients with diabetes mellitus in the DM‐INSULIN study,75 patients with T2D and mixed dyslipidemia in the DM‐DYSLIPIDEMIA study,77 individuals with prediabetes and normoglycemia,72 and those with and without dysglycemia or metabolic syndrome 73.…”
Section: Safety Of Pcsk9 Inhibitors In Patients With Diabetes Mellitusupporting
confidence: 70%
“…Findings were consistent in the prespecified diabetes mellitus subanalysis of FOURIER, which analyzed 11 031 patients with diabetes mellitus versus 16 533 patients without diabetes mellitus; compared with placebo, median LDL‐C levels were reduced by 57% in those with diabetes mellitus and by 60% in those without diabetes mellitus 71. Other subanalyses of ODYSSEY and PROFICIO phase 3 trials showed that LDL‐C reductions were also similar in those with and without prediabetes,72 impaired fasting glucose, and metabolic syndrome (Table).…”
Section: Lipid‐lowering Efficacy Of Pcsk9 Inhibitors In Patients Withsupporting
confidence: 59%
See 3 more Smart Citations